2020
DOI: 10.3390/agronomy10091334
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop for a Sustainable Viticulture: Effects on Soil Properties and Table Grape Production

Abstract: Cover crops are increasingly adopted in viticulture to enhance soil quality and balance the vegetative and reproductive growth of vines. Nevertheless, this sustainable practice has been only recently used for table grape viticulture, with results often contrasting. The aim of this study was to assess the effect of a fescue (Festucaarundinacea Schreb.) cover crop on soil quality, yield, and grape qualitative parameters in a table grape vineyard (cv “Italia”) located in southern Italy, comparing results with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 39 publications
4
20
1
Order By: Relevance
“…Our results are in accordance with the literature. Numerous studies found a sharp increase in SOM under mulched groundcovers as compared to tilled soil [13,[66][67][68]. Still in agreement with our results, Novara et al (2020) found a very limited and non-significant increase in SOM following eight years of faba bean CC incorporated in spring.…”
Section: Effects Of Soil Management On Soil Biological Quality Indexsupporting
confidence: 92%
“…Our results are in accordance with the literature. Numerous studies found a sharp increase in SOM under mulched groundcovers as compared to tilled soil [13,[66][67][68]. Still in agreement with our results, Novara et al (2020) found a very limited and non-significant increase in SOM following eight years of faba bean CC incorporated in spring.…”
Section: Effects Of Soil Management On Soil Biological Quality Indexsupporting
confidence: 92%
“…Similar results were obtained in wine-producing regions in the state of Santa Catarina, Brazil [65]. In the study by Gatullo et al [72], the SOC content in a table grape vineyard in southern Italy was 2.86 g kg −1 . Similar results were recorded by Dogan and Gülser [54] in a soil study in the Menderes district of Izmir, Turkey, where the SOC content was in the range of 2.70-14.91 g kg −1 .…”
Section: The Soc Content For Different Land Usessupporting
confidence: 81%
“…This, in turn, decreases the mean residence time of soil C by almost 50%, with detrimental effects on long-term C sequestration in agricultural soils. In contrast, NT + CC was shown to enhance soil fertility, stabilize soil structure, and increase soil C and N storage [ 23 , 24 , 25 , 26 , 27 ]. However, NT sometimes lead only to a soil C redistribution rather than a net C storage increase [ 28 ].…”
Section: Introductionmentioning
confidence: 99%